Experience of the School of Library, Documentation and Information in Developing Databases with Microisis Computer Program Version 3.0 - Miranda Arguedas, Alice (1993)
In the field of librarianship, thought should be given to normalizing processes, following the rules that make registers uniform anywhere in the world and that allow communication with other information units and clients.